2021
DOI: 10.3390/jrfm14020072
|View full text |Cite
|
Sign up to set email alerts
|

ESG Reporting and Analysts’ Recommendations in GCC: The Moderation Role of Royal Family Directors

Abstract: This study examines whether financial analysts consider or incorporate the environmental, social and governance disclosures (thereafter ESG) in their recommendations. We then test whether royal family directors affect this relation. Using a dataset from six Gulf Cooperation Council (GCC) countries, we find evidence that analysts’ recommendations are influenced by ESG information. Further, we find the political connection negatively moderates the relationship between sell-side analysts’ recommendations and ESG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 53 publications
6
45
1
Order By: Relevance
“…A qualitative study is needed to understand the motivations of tax avoidance in Omani financial institutions and to gain deeper insights into the experiences of AC chair and directors in their advisory or monitoring roles. In addition, Oman is one of the GCC countries that is characterized by royal families that might be involved in different business activities (Alazzani et al 2021). It would be interesting to explore the moderating role of the royal family directors on overlapped AC chair/director-tax avoidance relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study is needed to understand the motivations of tax avoidance in Omani financial institutions and to gain deeper insights into the experiences of AC chair and directors in their advisory or monitoring roles. In addition, Oman is one of the GCC countries that is characterized by royal families that might be involved in different business activities (Alazzani et al 2021). It would be interesting to explore the moderating role of the royal family directors on overlapped AC chair/director-tax avoidance relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Muslu et al (2019) developed a disclosure score based on textual analysis of CSR report narratives and found that CSR reporters with high disclosure scores are associated with more accurate forecasts. Using the Gulf Cooperation Council countries, Alazzani et al (2021) documented a positive relationship between analysts' recommendations and ESG disclosure and found that analysts assess ESG disclosure in firms with political connections as a strategic compliance. Berkan et al (2021) investigate the relationship between corporate social irresponsibility and financial analysts' performance and document that analysts tend to underestimate the effects of bad behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ESG covers the three main areas: environment, social and governance. ESG ratings assess areas ranging from sustainability to corporate governance (Alazzani et al, 2021). From the perspective of information asymmetry, ESG ratings not only provide extra nonfinancial information but also complement the existing financial information, which provides incrementally useful information to investors and financial analysts.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations